HUBUNGAN MINDSET TERHADAP MOTIVASI BELAJAR PESERTA DIDIK SEKOLAH DASAR DI DEPOK - Ernawati Ernawati; Nur Syarifah; Rini Yaumi Habibah; Feni Kurniawati Ardah (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2023)
This study aims to determine the relationship between mindset and learning motivationelementary school students and find out the obstacles to learning motivation and look for thesolution. The type of research used in this research is quantitative research.The population in this study was grade V and grade VI elementary school in Depok with the number of samples is 112 students for the academic year 2022/2023. Data collection techniques that used are questionnaires and observations. From the calculation results obtained a correlation test of 0.570 which is in the medium interval. This shows that the relationship between mindset and learning motivation. The obstacles come from students who less motivated when learning in class and outside the classroom. The solution is awareness of students, conducted training for teachers and parents, teachers foster motivation students by creating a pleasant atmosphere, linking learning with everyday life.